Order Matters: Rating Service Professionals First Reduces Tipping Amount - Chen, Jinjie; Xu, Alison Jing; Rodas, Maria A.; Liu, Xuefeng (Journal of Marketing, 2023)
As customer ratings have become ubiquitous and digital platforms can directly request ratings and tips from customers, it is important to understand how a customer rating influences tipping. The authors investigate whether, how, why, and when the order of rating and tipping affects both consumer behaviors in seven studies, including one quasi-field experiment, one archival data analysis, one randomized field experiment, and four randomized lab experiments. They show that asking customers to rate a service professional before tipping negatively impacts the tip amount but that tipping first does not affect subsequent rating scores. The authors propose that the negative effect of rating on tipping occurs because, when rating a service professional first, customers categorize their feedback as a reward for the service professional, which partially alleviates the felt obligation to tip, resulting in a smaller tip. This negative effect is more evident when customers (1) tip from their own pocket, (2) have higher categorization flexibility, or (3) perceive that the service professional benefits from the rating. Moreover, highlighting the consistency motivation after rating but before tipping can attenuate this effect. These boundary conditions not only support the proposed mechanism and evaluate alternative processes but also have significant practical implications.